Public Speaking Training in Developing the Communication Skill of PKK Community in Ngidam Muncar, Susukan, Semarang - Itasari, Andri Astuti; Hastuti, Nurnawati Hindra; Maria, Dewi (Asian Journal of Community Services, 2024)
This community service is entitled "Public Speaking Training in Developing Communication Skills in the PKK Community in Muncar Village, Susukan, Semarang. The role of the PKK Association is considered important to participate in developing and marketing this tourism village to outsiders by communicating about the tourism village to outsiders. The output target is that partners are able to carry out training on public speaking, so that this step indirectly contributes to increasing the promotion of the tourist village. The results of the activity showed that service participants experienced increased public speaking knowledge and skills, were able to manage emotions and nervousness, and tried to appear confident in public so that effective communication techniques could be created.